Differences in improving learning outcomes and student learning motivation - S. Sudirman; Kms. Muhammad Amin Fauzi; Anita Yus (Inovasi Kurikulum, 2024)
The Mathematics Learning Grade IV at SD Negeri 1 Syamtalira Bayu has yet to reach the indicators. Ideally, learning mastery occurs when 76% of students score above the Kriteria Ketuntasan Minimal (KKM). This study aims to determine the differences in students' learning outcomes and motivation through teaching using the Contextual Teaching and Learning (CTL) and discovery learning models. This quasi-experimental study involved two Grade IV-B and IV-A classes as the research sample. The research instruments used were tests and a motivation questionnaire. Data analysis was conducted using t-test and N-Gain analysis. Based on the results of the analysis, it was found that students' learning outcomes using the CTL model were higher than those using the discovery learning model. The learning motivation of students in the CTL model class was higher than in the discovery learning model class. Based on the research, the CTL model can improve students' learning outcomes and motivation. AbstrakPembelajaran Matematika di kelas IV di SD Negeri 1 Syamtalira Bayu belum mencapai indikator keberhasilan. Ketuntasan belajar idealnya terjadi apabila 76% dari keseluruhan peserta didik dikatakan tuntas atau mendapatkan nilai di atas KKM. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa melalui pengajaran dengan model Contextual Teaching and Learning (CTL) dan model discovery learning. Mengetahui motivasi belajar siswa yang diajarkan dengan model pembelajaran CTL dan model discovery learning. Penelitian ini merupakan penelitian eksperimen semu (quasi eksperiment). Sampel penelitian ini terdiri dari 2 kelas dari siswa kelas IV-B dan IV-A. Instrumen yang digunakan adalah tes dan angket motivasi belajar. Analisis data dilakukan dengan uji statistik uji-t dan N-Gain. Berdasarkan hasil analisis diperoleh hasil belajar siswa dengan model CTL lebih tinggi dari model discovery learning. Motivasi belajar siswa pada kelas model CTL lebih tinggi dari kelas model Discovery Learning. Berdasarkan hasil penelitian, model CTL dapat meningkatkan hasil belajar dan motivasi belajar siswa.Kata Kunci: Hasil belajar, motivasi belajar, model CTL, model discovery learning